2023
DOI: 10.3390/antibiotics12081246
|View full text |Cite
|
Sign up to set email alerts
|

Role of Antimicrobial Resistance in Outcomes of Acute Endophthalmitis

Aaron Yap,
Sharmini Muttaiyah,
Sarah Welch
et al.

Abstract: Background: This study explores local trends in antimicrobial resistance and its influence on long-term visual outcomes following treatment with broad-spectrum empiric intravitreal antibiotics. Methods: All patients undergoing intraocular sampling for endophthalmitis from Auckland between January 2006–May 2023 were included. The impact of antimicrobial resistance on the final visual outcome was analysed using logistic regression models. Results: 389 cases of endophthalmitis were included, and 207 eyes (53.2%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Pediatric data have indicated antibiotic resistance in infections secondary to staphylococci or pneumococcal organisms, and similar multidrug resistance among staphylococci [ 64 ]. Local and regional US studies have also showed similar resistance trends, with a peak methicillin-resistant S. aureus (MRSA) prevalence prior to 2015, with a slight decreasing trend afterwards [ 48 ].…”
Section: Antimicrobial Resistance Associated With Endophthalmitismentioning
confidence: 99%
“…Pediatric data have indicated antibiotic resistance in infections secondary to staphylococci or pneumococcal organisms, and similar multidrug resistance among staphylococci [ 64 ]. Local and regional US studies have also showed similar resistance trends, with a peak methicillin-resistant S. aureus (MRSA) prevalence prior to 2015, with a slight decreasing trend afterwards [ 48 ].…”
Section: Antimicrobial Resistance Associated With Endophthalmitismentioning
confidence: 99%